Exploring basal metabolic rate and dietary adequacy in twin pregnancies: the VENERE study - Dinu, Monica; Napoletano, Antonia; Giangrandi, Ilaria; Lotti, Sofia; Ruotolo, Agostino; Renda, Irene; Nardone, Luca; Paternò, Irene; Seravalli, Viola; Tristan Asensi, Marta; Pagliai, Giuditta; Colombini, Barbara; et al. (Nutrition & metabolism, 2024)
Background Twin pregnancies present unique challenges in maternal healthcare. However, current guidelines primarily address singleton pregnancies, resulting in a knowledge gap regarding their specific metabolic and dietary needs. This study aimed to follow women with twin pregnancies through all three trimesters, assessing basal metabolic rate (BMR), dietary intake, and diet quality. Methods A two-year prospective observational study was conducted at AOU Careggi Hospital, Florence, Italy, involving 35 twin-pregnant women, with 32 completing the study. Participants underwent calorimetric, anthropometric, and dietary assessments during the first (8–13 weeks), second (14–27 weeks), and third trimesters (28–34 weeks). BMR was measured using indirect calorimetry and compared with predictive equations. Dietary intake was evaluated using 7-day food diaries and the Medi-Lite adherence score. Results Indirect calorimetry revealed an increase in BMR by 16%, rising from 1479 ± 196 kcal in the first trimester to 1733 ± 224 kcal in the third trimester. Hronek’s equation, previously validated for singleton pregnancies, was identified as the most accurate predictive tool for estimating BMR. Dietary analysis revealed that mean daily energy intake increased from 1660 ± 244 kcal in the first trimester to 1889 ± 262 kcal in the third trimester, consistently below recommendations, with insufficient macro- and micronutrient consumption. Poor diet quality was characterized by low intake of fruits, vegetables, legumes, and fresh fish, and high consumption of processed meats, cheese, and sugar-sweetened beverages. Adherence to the Mediterranean diet was moderate across all three trimesters. Conclusions This study highlights the increased energy demands and nutritional inadequacies in twin pregnancies, underscoring the need for tailored dietary guidelines and interventions.